Adicción a las redes por internet y habilidades sociales en adolescentes, Trujillo - 2016 - Damas Narciso, Fiorella Karina (2018)
The present study investigation of descriptive type, correlational of traverse court, carried out at the National Educational Institution Victor Andrés Belaunde de Trujillo - 2016; with the aim of determining the relationship of addiction to Internet networks and affectation in social skills: assertiveness, communication, selfesteem and decision-making in adolescents. The sample consisted of 220 adolescents from first to fifth high school. For data collection, two instruments were used: the questionnaire on Addiction to Social Networks elaborated by Escurra and Salas (2014) and the Social Skills Assessment Test developed by MINSA and the Honorio Delgado Institute of Mental Health (1998). The obtained information was processed and analyzed in the program SPSS version 21 and presented in single and double entry tables, to determine the relationship between the variables the Chi square statistical test was used. Concluding that: 25.5% of adolescents do not present addiction, 28.2% have mild addiction, 22.3% moderate addiction and 24.1% severe addiction. In social skills, 57.3% presented average assertiveness, 48.6% average communication, 44.1% average selfesteem and 78.2% average decision-making, with a significant relationship between internet addiction and social skills